Awareness and Level of Implementation of Industry 4.0 and Society 4.0 Concepts in Selected Polish SMEs - Katarzyna ZIELIŃSKA (Communications of International Proceedings, 2021)
The fourth industrial revolution is not a distant future, but rather - the present we live in. Society is facing great opportunities, as well as fundamental social and economic changes. The “Society 4.0” and “Industry 4.0” terms are still foreign to some people in Poland and abroad and in some cases, they are even considered to be rather concerning. Therefore, within the scope of this dissertation, the author elaborates on the specificity of “Society 4.0” and “Industry 4.0” concepts, as well as touches upon the issue of their impact on the organizations and the assessment of the current situation of Polish enterprises during the fourth industrial revolution. In order to achieve the set goal, a survey has been conducted aiming at assessing the readiness of enterprises to adopt the concepts of Industry 4.0 and Society 4.0, as well as to include them in their business strategies. Unfortunately, most of the surveyed companies have not been aware of “Industry 4.0” and “Society 4.0” concepts. What is more, a very small percentage of the respondents has declared that they feel they are innovators or users of modern technological solutions. It has been mainly caused by the lack of adequate financial background.
Keywords: Industry 4.0; industrial revolution; Society 4.0